What Drives Housing Outcomes in Australia? Understanding the Role of Aspirations, Household Formation, Economic Incentives and Labour Market Interactions - Hendershott, P.H.; Watson, R; Wood, G; Flatau, P (My University, 2003)
The sequence of housing stages that an individual moves through over their lifetime forms the ‘housing career’ of that individual. While each housing career follows a unique path, a set of general forces act to influence the overall direction taken by individual housing careers. These drivers include: − Housing tenure preferences and housing market signals (house prices, rents etc.); − Household formation aspirations and outcomes; − Labour market effects (wages, employment, unemployment, and retirement); − Lifetime wealth accumulation objectives, and, − Housing assistance, income support, tax, and welfare programs. • In this project, we map out how these (and other) drivers influence the trajectory of Australian housing careers. We focus attention on three distinct life-cycle stages: (1) Early adulthood when the first, independent housing career transitions are made (ages 15-34); (2) the middle age stage (ages 35-49); and (3) The mature phase of the life cycle (ages 50- 69). • The aim of the study is to increase our understanding of what drives housing outcomes in Australia and what determines the structure of Australian housing careers.
Australian Housing and Urban Research Institute, Positioning Paper
Keywords: Housing; Housing, communities and neighbourhoods; Housing, communities and neighbourhoods